2022
DOI: 10.3389/fbioe.2022.1042625
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in hydrogels-based osteosarcoma therapy

Abstract: Osteosarcoma (OS), as a typical kind of bone tumors, has a high incidence among adolescents. Traditional tumor eradication avenues for OS such as chemotherapy, surgical therapy and radiation therapy usually have their own drawbacks including recurrence and metastasis. In addition, another serious issue in the treatment of OS is bone repair because the bone after tumor invasion usually has difficulty in repairing itself. Hydrogels, as a synthetic or natural platform with a porous three-dimensional structure, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…The use of hydrogels as a repository for drug delivery is an approach that has gained attention in the last decade as it proves to be an effective targeted therapy for localized pathology [ 77 , 79 ]. Additionally, hydrogels have the capability of being integrated with other drug delivery systems, such as liposomes or microspheres, which synergistically allows for better performance [ 80 ]. For example, Wu et al (2018), photo crosslinked gemcitabine (GEM) hydrochloride loaded liposomes with a gelatin methacryloyl (GelMA) hydrogel to test its efficacy for osteosarcoma ablation [ 81 ].…”
Section: Hydrogels For Osteosarcoma Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The use of hydrogels as a repository for drug delivery is an approach that has gained attention in the last decade as it proves to be an effective targeted therapy for localized pathology [ 77 , 79 ]. Additionally, hydrogels have the capability of being integrated with other drug delivery systems, such as liposomes or microspheres, which synergistically allows for better performance [ 80 ]. For example, Wu et al (2018), photo crosslinked gemcitabine (GEM) hydrochloride loaded liposomes with a gelatin methacryloyl (GelMA) hydrogel to test its efficacy for osteosarcoma ablation [ 81 ].…”
Section: Hydrogels For Osteosarcoma Therapymentioning
confidence: 99%
“…Some of the biggest challenges for osteosarcoma treatment are chemoresistance and metastasis prevention [ 124 ]. Studies have shown that hydrogels can treat tumors due to their biocompatibility and porous structures [ 80 ]. Hydrogels can be loaded with tumor therapy drugs that can be inserted intravenously to replace systemic chemotherapy.…”
Section: Future Applications Of Hydrogels Designed For Osteosarcoma T...mentioning
confidence: 99%
“…The standard chemotherapeutic regimen, known as MAP therapy, encompasses methotrexate, doxorubicin, and cisplatin 4 . Notably, metastasis most commonly occurs within the lung parenchyma, significantly impacting clinical outcomes in a negative manner 5 . Presently, the effectiveness of targeted medications remains limited due to the marked heterogeneity of OS 6 .…”
Section: Introductionmentioning
confidence: 99%
“…OS cells grow in a permissive local microenvironment which modulates their behavior and facilitates all steps in tumor development (e.g., proliferation/quiescence, invasion/migration, drug resistance) [ 4 , 13 15 ] and contributes to their intrinsic heterogeneity [ 16 , 17 ••]. The lung parenchyma is the most common metastatic site in OS, and metastatic foci are frequently associated with a poor clinical outcome [ 7 , 9 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The conventional treatment for OS is based on a sequential approach that combines chemotherapy and surgery [ 4 ]. Due to the particular radioresistance of OS, radiotherapy is only proposed for tumors in high-risk locations, or to reduce the risk of recurrence after surgery [ 7 9 , 18 20 ]. Despite the increase in clinical trials in the last 4 decades, cure rates for OS have not improved.…”
Section: Introductionmentioning
confidence: 99%